Application of post-emergent herbicides for weed control in rice crop (Oryza sativa L.) - Suárez Baque, Doris Lissette; Durán Mera, Christian Alejandro (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2023)
The present investigation was carried out in the Petrillo campus, Cantón Nobol, province of Guayas. The objective of the research was to carry out a control of weeds in the rice crop (Oryza sativa L.) with the application of postemergence herbicides, a completely randomized block experimental design (DBCA) was used, with 4 treatments and 3 repetitions, giving a total of 12 experimental plots. The efficacy of the herbicides was evaluated at 5, 10 and 15 days, toxicity caused in the crop plus the morphology and yield. The herbicide (Quinclorac) obtained better results based on the control of Echinochloa colona and Ipomoea spp, with an efficacy of 90% and a yield of 4552.86 kg/ha was achieved, (Metamifop) was the least efficient
Keywords: Herbicide, quinclorac; rice; weeds